AB1086 An Eular Study Group Pilot Study on Reliability of "Simple" Capillaroscopic Definitions to Describe Capillary Morphology in Rheumatic Diseases. (9th June 2015) - Smith, V.; Beeckman, S.; Herrick, A.; Decuman, S.; Deschepper, E.; Riccieri, V.; Sulli, A.; De Keyser, F.; Müller-Ladner, U.; Ingegnoli, F.; Cutolo, M.
Abstract : Background: The established EULAR study group on Microcirculation in Rheumatic Diseases (RD) aims to build an international network of centres of excellence to facilitate collaboration and exchange knowledge within Europe. One of its aims is to study natural evolution of microvascular morphology in RD. To this end standardisation of morphological interpretation/nomenclature across diseases is paramount. Objectives: To propose simple capillaroscopic definitions for interpretation of single capillaroscopic morphologies and assess their interobserver reliability. Methods: The simple definitions proposed to assess morphology were: 1) "normal": hairpin, tortuous or crossing 1 ; 2) "abnormal": not hairpin, tortuous or crossing 1 ; 3) "not evaluable": whenever rater doubted in classifying between normal and abnormal. Based upon an aimed kappa of 0.80 and equal default prevalences of normal (0.4) and abnormal (0.4) capillary morphology and a smaller proportion of not evaluable (0.2) capillaries, 87 capillaries evaluated by two independent raters were necessary to obtain a half width of the 95% confidence interval (CI) of no larger than 0.2. Consequently, 90 randomly selected single capillaries were presented in 2 batches of 45 single capillaries to 3 groups of raters: experienced independent raters (AH, FI, VR, AS, VS [gold standard]) n=5; attendees to the 6th EULAR course on capillaroscopy, n=34; novices after a 1 hour institutional course at the Ghent University hospital, n=11. Inter-rater agreement was assessed by calculation of proportion of agreement and by kappa coefficients. Results: Mean kappa was 0.49 (95% CI: 0.44-0.54) for expert raters, 0.40 (0.36-0.44) for attendees and 0.46 (0.41-0.52) for novices, with overall agreements of 67% (63-71), 63% (60-65) and 67% (63-70) respectively. Comparing only "normal" vs. "abnormal and not evaluable" capillaries did increase the kappa: 0.51 (0.37-0.65), 0.53 (0.49-0.58), and 0.55 (0.49-0.62). Conclusions: This study shows moderate reliability of "simple" capillaroscopic definitions to describe morphology of individual capillaries by rheumatologists with different expertise on the topic. Further optimization of morphologic interpretation is ongoing. References: Kabasakal Y, et al. Ann Rheum Dis. 1996;55(8):507-12. Cutolo M, Smith V. Nailfold Capillaroscopy. In: Wigley FM et al. editors. Raynaud's phenomenon: A guide to pathogenesis and treatment. New York: Springer Science+Business Media; 2015. Disclosure of Interest: None declared